Regulation of the Zinc Deficiency Response in the Legume Model Medicago truncatula - Liao, Feixue; Lilay, Grmay Hailu; Castro, Pedro Humberto; Azevedo, Herlander; Assunção, Ana G. L. (Frontiers in Plant Science, 2022)
The zinc deficiency response in Arabidopsis thaliana is regulated by F-group basic region leucine-zipper (F-bZIP) transcription factors, and there is evidence of evolutionary conservation of this regulatory network in land plants. Fundamental knowledge on the zinc homeostasis regulation in crop species will contribute to improving their zinc nutritional value. Legumes are protein-rich crops, used worldwide as part of traditional diets and as animal forage, being therefore a good target for micronutrient biofortification. Here, we identified F-bZIP transcription factors in representative legume species and functionally characterized the two F-bZIPs from Medicago truncatula. Results indicate that MtFbZIP1 is the functional homolog of A. thaliana bZIP19 and bZIP23, while MtFbZIP2 does not play a role in the zinc deficiency response. Additionally, analysis of M. truncatula genes from the Zrt/Irt-like protein (ZIP) family of zinc transporters or encoding nicotianamine synthase enzymes that produce the zinc ligand nicotianamine, support the conservation of the F-bZIP-regulated zinc deficiency response in M. truncatula. Phylogenetic analysis of F-bZIP homologs enriched in legume species reinforces the branching into two groups, with MtFbZIP1 and MtFbZIP2 mapping in Groups 1 and 2, respectively. This phylogeny combined with the functional characterization of MtFbZIPs supports the suggested conservation of the zinc deficiency response associated with Group 1 F-bZIPs, and the more variable evolutionary paths associated with Group 2. Overall, we provide novel insight on the mechanisms of response to zinc deficiency in M. truncatula, which contributes to developing strategies for improving zinc content in legume crops.